Electroconvulsive Therapy and Risk of Dementia—A Nationwide Cohort Study in Taiwan - Chu, Ching-Wen; Chien, Wu-Chien; Chung, Chi-Hsiang; Chao, Pei-Chun; Chang, Hsin-An; Kao, Yu-Chen; Chou, Yu-Ching; Tzeng, Nian-Sheng (Frontiers in Psychiatry, 2018)
Background: Electroconvulsive therapy (ECT) is an effective treatment for schizophrenia, bipolar disorder, and major depressive disorder. Temporary memory loss may occur after ECT. However, the association between ECT in patients with schizophrenia, bipolar disorder, and major depressive disorder, and the risk of dementia has yet to be examined. This study aimed to clarify whether ECT is associated with the risk of dementia after ECT in patients with schizophrenia, bipolar disorder, and major depressive disorder, using the National Health Insurance Research Database (NHIRD) of Taiwan. Methods: A total of 3,796 enrolled participants (schizophrenia, 46.68%; bipolar disorder, 11.77%; and major depressive disorder, 41.55%) with 994 patients who had received ECT and 2,982 controls matched for sex and age, between January 1, and December 31, 2000, , from the Longitudinal Health Insurance Dataset of 2000-2015, were selected from the NHIRD of Taiwan. Fine and Gray’s survival analysis was used to explore the hazard ratio (HR), and 95% confidence interval (CI), for the risk of ECT being associated with the risk of developing dementia during the 15 years of follow-up. Results: Of the study patients, 45 (4.53%) developed dementia when compared to 149 (5.0%) in the control group, without significant difference (p = 0.308). Fine and Gray’s survival analysis revealed that the study patients were not associated with an increased risk of dementia, and the adjusted HR was 0.633 (95% CI = 0.448 – 1.895, P =0.304), after adjusting for sex, age, monthly income, urbanization level, geographic region, and comorbidities. In this study, the sensitivity test revealed that the ECT cohort was not associated with the increased risk of dementia within 0—3 years, 3—6 years, and ≧ 6 years after ECT. The ECT was not associated with the risk of dementia, except for patients who were older than 65 years-old, and experienced prolonged seizures, in-hospital delirium, and acute stroke. Conclusion: This study supports that ECT was not associated with the increased risk of dementia in patients with schizophrenia, bipolar disorder, and major depressive disorder, using the NHIRD, except for ECT in older patients, or prolonged seizures, in-hospital delirium, and acute stroke.